Compensation for medical incidents as a result of out-of-court conciliatory proceedings by voivodship boards - Susło, Robert; Paplicki, Mateusz; Benedik, Antoni; Drobnik, Jarosław (Family Medicine & Primary Care Review, 2020)
There is a growing gap between the public’s imagination of medicine’s capabilities, the range of medical services really available to the average patient, and the actual results of medical procedures. Many patients feel deceived by, neglected by, or disappointed with medicine, health institutions, and medical staff. Patients’ grievances result in an increasing number of legal claims in courts and politicians introduce harsher legal regulations targeting delinquent or negligent medical professionals. The aim of the article is to discuss resulting problems and available solutions. The term “defensive medicine” describes adjustments made by medical staff to their professional activities primarily to secure themselves from claims and not to benefit the patient, involving risk reduction and risk avoidance. It is estimated that medically unjustified procedures driven by fears of malpractice suits account for even as much as 20% of total healthcare costs. Primary care physicians are among the greatest contributors in that they tend to overcautiously order otherwise unneeded hospitalizations, generating significant secondary costs. In Poland, the Patient Rights and Ombudsman Act of 6 November 2008, with its 2011 amendment, introduced a new way for hospitalized patients who have suffered medical harm to seek compensation without costly, time-consuming, blame-based court proceedings. Although - unlike in courts - claimants do not need to provide decisive evidence of the claim’s accuracy, but only back it up adequately, the new administrative quasi-court proceedings has not gained popularity as often it lasts longer than expected and rather low compensation proposed tend to be considered unsatisfactory by claimants.